Dropout in Higher Education A Review and Theoretical Synthesis of Recent Research - Tinto, Vincent; Cullen, John; Columbia Univ., New York, NY. Teachers College ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This document presents a review and theoretical synthesis of recent research on dropouts in higher education. The first chapter deals with defining dropouts from college, and in considering the various meanings applied to that term, suggests some needed modifications in the definition. The second chapter reviews recent data on dropouts in order to estimate both the effect of ability and social status on current rates of dropout and the degree to which rates of dropout have changed since 1965. The third and forth chapters deal respectively with the development of the basic theoretical model which seeks to explain dropout as an interactive process between the individual and the institution, and with the synthesis of recent research on dropout within that theoretical model. The fifth and final chapter utilizes the findings of the preceding two chapters in order to develop a modified definition which seeks to distinguish voluntary from nonvoluntary dropout and transfer from the permanent dropout from higher education. An extensive bibliography is included. (Author/MJM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Office of Planning, Budgeting, and Evaluation.
Contract Number: OEC-0-73-1409.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Dropout Characteristics; Dropout Rate; Dropout Research; Dropouts; Higher Education; Literature Reviews; Models